Promoting menstrual cups as a sustainable alternative: a comparative study using a labeled discrete choice experiment - Prima Citta, Sitadhira; Uehara, Takuro; Cordier, Mateo; Tsuge, Takahiro; Asari, Misuzu (Frontiers in Sustainability, 2024)
Plastic pollution is a global issue that endangers both human health and the ecosystem. Although interest in sustainable alternatives to single-use plastics has grown, their adoption has been insufficient, and menstrual products are no exception. Disposable menstrual products, such as sanitary napkins, continue to dominate over sustainable options like menstrual cups (MCS). Although studies on women’s perceptions and attitudes toward menstrual hygiene management have abounded, there is a lack of research on the development of promotional strategies for sustainable menstrual products. This study aims to fill this research gap by investigating consumers’ decision-making process in the face of a real-life option regarding menstruation products. In this comparative study, we conducted a labeled discrete choice experiment on consumers in Japan (n = 1,929), Indonesia (n = 2,031), and France (n = 2,067) to reveal their preferences for sanitary napkins, tampons, and MCs. The respondents from each country were divided into three groups (one control group and two treatment groups with information provided). The results showed that in all countries, the information regarding the cost-effectiveness of MCs (i.e., per-use cost) was unequivocally significant, whereas information about their health and environmental benefits was not. Access to free MCs can contribute to their adoption and alleviation of period poverty in all countries, with a relatively moderate acceptance in Japan. The results also showed variations across countries in consumer characteristics (attitude towards menstruation, innovation-friendliness, and green consumption) and the use and perceptions of MCs. Hence, tailored promotional strategies should be considered for each market.